A dynamic cell entry pathway of respiratory syncytial virus revealed by tracking the quantum dot-labeled single virus. Issue 23 (31st May 2017) - Zheng, Lin Ling; Li, Chun Mei; Zhen, Shu Jun; Li, Yuan Fang; Huang, Cheng Zhi
Abstract : A quantum dot based single-particle tracking approach is used to monitor the intracellular trafficking of single respiratory syncytial virus particles in living cells. Abstract : Studying the cell entry pathway at the single-particle level can provide detailed and quantitative information for the dynamic events involved in virus entry. Indeed, the viral entry dynamics cannot be monitored by static staining methods used in cell biology, and thus virus dynamic tracking could be useful in the development of effective antiviral strategies. Therefore, the aim of this work was to use a quantum dot-based single-particle tracking approach to monitor the cell entry behavior of the respiratory syncytial virus (RSV) in living cells. The time-lapse fluorescence imaging and trajectory analysis of the quantum dot-labeled RSV showed that RSV entry into HEp-2 cells consisted of a typical endocytosis trafficking process. Three critical events during RSV entry were observed according to entry dynamic and fluorescence colocalization analysis. Firstly, RSV was attached to lipid rafts of the cell membrane, and then it was efficiently delivered into the perinuclear region within 2 h post-infection, mostly moving and residing into the lysosome compartment. Moreover, the relatively slow velocity of RSV transport across the cytoplasm and the formation of the actin tail indicated actin-based RSV motility, which was also confirmed by the effects of cytoskeletal inhibitors. Taken together, these findings provided new insights into the RSV entry mechanism and virus–cell interactions in RSV infection that could be beneficial in the development of antiviral drugs and vaccines.